Plasma D-Dimer Concentrations and Risk of Intracerebral Hemorrhage: A Systematic Review and Meta-Analysis - Zhou, Zhike; Liang, Yifan; Zhang, Xiaoqian; Xu, Junjie; Kang, Kexin; Qu, Huiling; Zhao, Chuansheng; Zhao, Mei (Frontiers in Neurology, 2018)
Background: The aim of our meta-analysis was to evaluate the association between plasma d-dimer and intracerebral hemorrhage (ICH). Methods: Embase, Pubmed, and Web of Science were searched up to the date of March 19th, 2018, and manual searching was used to extract additional articles. Standard mean difference (SMD) with 95% confidence intervals (CI) was calculated to evaluate d-dimer levels. Results: Thirteen studies including 891 ICH patients and 1573 healthy controls were included. Our results revealed that higher levels of d-dimer were displayed in ICH patients than those in healthy controls (95% CI=0.98-2.00, p<0.001). Subgroup analysis based on continent of Asia and Europe, sample size, as well as age in relation to d-dimer levels between ICH patients and healthy controls did not change the initial observation; whereas no differences of d-dimer levels were found between ICH and controls in America. Conclusions: This meta-analysis revealed that high level of d-dimer is associated with the risk of ICH. Plasma d-dimer is suggested to be a potential biomarker for patients with ICH in Asia and Europe rather than in America. There were no impact of sample size-related differences and age-related diversities on the risk of ICH with respect to d-dimer levels.